2013
DOI: 10.1093/rheumatology/kes414
|View full text |Cite
|
Sign up to set email alerts
|

Ayurvedic medicine offers a good alternative to glucosamine and celecoxib in the treatment of symptomatic knee osteoarthritis: a randomized, double-blind, controlled equivalence drug trial

Abstract: Clinical Drug Trial Registry-India, www.ctri.nic.in, CTRI/2008/091/000063.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 23 publications
0
70
0
Order By: Relevance
“…A comparison of Ayurvedic formulations (extracts of Tinospora cordifolia , Zingiber officinale , Emblica officinalis and Boswellia serrata ), glucosamine sulfate 2 g daily and celecoxib 200 mg daily in 440 Indian patients with knee OA over a 24‐week period showed that pain relief was within the equivalence range. However, seven patients using Ayurvedic intervention were withdrawn due to increased serum glutamic pyruvic transaminase, which normalized when the intervention was stopped 24. These findings indicate that safety assessments of alternative medications are warranted, together with a definition of bioequivalence of efficacy in clinical studies.…”
Section: Discussionmentioning
confidence: 97%
“…A comparison of Ayurvedic formulations (extracts of Tinospora cordifolia , Zingiber officinale , Emblica officinalis and Boswellia serrata ), glucosamine sulfate 2 g daily and celecoxib 200 mg daily in 440 Indian patients with knee OA over a 24‐week period showed that pain relief was within the equivalence range. However, seven patients using Ayurvedic intervention were withdrawn due to increased serum glutamic pyruvic transaminase, which normalized when the intervention was stopped 24. These findings indicate that safety assessments of alternative medications are warranted, together with a definition of bioequivalence of efficacy in clinical studies.…”
Section: Discussionmentioning
confidence: 97%
“…[21] As one of the ingredient in polyherbal formulation, Boswellia serrata significantly reduced knee pain and improved knee function which were equivalent to glucosamine and celecoxib in a 6-month controlled study of knee OA. [22] In another ayurvedic study, a formulation (containing Curcuma longa and Boswellia serrata extracts) at 500 mg administered twice a day demonstrated to be more effective compared to celecoxib 100 mg twice a day for symptom scoring and clinical examination with good safety in OA patients. [23] In the present study, Boswellia serrata also has demonstrated a significant analgesic activity when compared to placebo even when administered as a single dose with good safety and tolerability.…”
Section: Discussionmentioning
confidence: 99%
“…For continuous outcomes with no standard deviation reported, we calculated standard deviations (SD), if possible, from standard errors (SEM), P values, or CIs. For four studies we converted the VAS data from a 10 cm scale to a 100 mm scale (Chopra 2013; Gupta 2011; Kuptniratsaikul 2011; Piscoya 2001), and for three studies we converted SEM to SD (Huber 1991; Maheu 2013; Piscoya 2001). …”
Section: Methodsmentioning
confidence: 99%